2019
DOI: 10.1177/1758835919853958
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet treatment as adjuvant to standard treatment of glioblastoma multiforme: a feasibility and safety study

Abstract: Background: High-grade glioma cells consume mainly glucose and cannot compensate for glucose restriction. Apoptosis may potentially occur under carbohydrate restriction by a ketogenic diet (KD). We explored the feasibility and safety of KD during standard treatment of chemoradiation in patients with glioblastoma multiforme. Methods: A full liquid KD induced ketosis within 2 weeks before start of chemoradiation. After 6 weeks, the KD was modified with solid foods and medium-chain-triglyceride emulsions and used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 39 publications
2
70
0
2
Order By: Relevance
“…Rapamycin was selected for the current animal study because it a) has the potential to be a successful anti-cancer drug when administered at doses known to be normo-glycemic in mice b) it may yet have utility in humans and c) has been an FDA approved drug since 1999 [12]. The principle of combining a ketogenic diet with other forms of anti-cancer chemotherapies for widely metastatic disease has been reported to have potential additive effects in mice [13,14], as well as in limited human studies [4,[15][16][17][18]. As above, rapamycin is not expected to induce hyperglycemia in our mouse model and we wished to determine if a KD would exert its cytotoxic effects even in the absence of hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Rapamycin was selected for the current animal study because it a) has the potential to be a successful anti-cancer drug when administered at doses known to be normo-glycemic in mice b) it may yet have utility in humans and c) has been an FDA approved drug since 1999 [12]. The principle of combining a ketogenic diet with other forms of anti-cancer chemotherapies for widely metastatic disease has been reported to have potential additive effects in mice [13,14], as well as in limited human studies [4,[15][16][17][18]. As above, rapamycin is not expected to induce hyperglycemia in our mouse model and we wished to determine if a KD would exert its cytotoxic effects even in the absence of hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Rapamycin was selected for the current animal study because it a) has the potential to be a successful anti-cancer drug when administered at doses known to be normo-glycemic in mice b) it may yet have utility in humans and c) has been an FDA approved drug since 1999 [11]. The principle of combining a ketogenic diet with other forms of anti-cancer chemotherapies for widely metastatic disease has been reported to have additive effects in mice [12] [13] [14], as well as in limited human studies [4] [15] [16] [17]. As above, rapamycin is not expected to induce hyperglycemia in our mouse model and we wished to determine if a KD would exert its cytotoxic effects even in the absence of hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“… 19 20 Also, ketogenic/low-carb nutritional regimes have recently been investigated in clinical studies enrolling overweight patients with type II diabetes 21 and patients suffering from glioblastoma. 22 These studies reported no adverse side effects, providing additional evidence that ketogenic/low-carb diets are feasible and safe.…”
Section: Introductionmentioning
confidence: 79%